2021
DOI: 10.3390/ijerph19010137
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Four Week, Randomized, Double-Blind, Placebo-Controlled Trial of Metformin for Antipsychotic-Induced Weight Gain in Patients with First-Episode Psychosis: A Pilot Study

Abstract: Excessive weight gain and cardiometabolic dysfunction are common and clinically relevant side effects of antipsychotic medications. In this pilot study, we aimed to establish the feasibility of using metformin and its effectiveness in managing antipsychotic-induced weight gain in patients with first-episode psychosis (FEP) on follow-up with the Singapore Early Psychosis Intervention Programme in a 24-week, randomized, double-blind, placebo-controlled trial, to ascertain the effects of metformin discontinuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Four studies ( 66–69 ) included patients diagnosed with bipolar disorder and other psychiatric disorders (DSM-IV), however in a negligible percentage: as an example, Agarwal et al 2 patients out of 30; Baptista et al 4 patients out of 80. In 5 trials ( 66 , 70–73 ) only overweight/obese patients were included, and 6 trials reported diabetes or prediabetes among the exclusion criteria ( 66 , 69 , 70 , 72 , 74 , 75 ). All studies, except Mondal et al ( 64 ), reported any other chronic disease (such as thyroid, liver or renal dysfunction, cardiovascular disease) and pregnancy among the exclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies ( 66–69 ) included patients diagnosed with bipolar disorder and other psychiatric disorders (DSM-IV), however in a negligible percentage: as an example, Agarwal et al 2 patients out of 30; Baptista et al 4 patients out of 80. In 5 trials ( 66 , 70–73 ) only overweight/obese patients were included, and 6 trials reported diabetes or prediabetes among the exclusion criteria ( 66 , 69 , 70 , 72 , 74 , 75 ). All studies, except Mondal et al ( 64 ), reported any other chronic disease (such as thyroid, liver or renal dysfunction, cardiovascular disease) and pregnancy among the exclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Clozapine, olanzapine, aripiprazole, and risperidone were the most used antipsychotics. In 3 trials the concomitant use of mood stabilizers, benzodiazepines and antidepressants was permitted ( 65 , 69 , 75 ). Lifestyle intervention involving diet and physical exercise was provided in 6 trials ( 65 , 66 , 68 , 72 , 76 , 77 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most prevention trials clarified their exclusion of people with diabetes, whereas trials to mitigate antipsychotic‐induced weight gain often included such patients. Trials aimed at reversing weight gain typically recruited patients who experienced weight gain of at least 10% bodyweight, although results from a recent pilot RCT conducted in Singapore that included 17 participants suggest that there may be benefits following first episode psychosis for patients with weight gain as low as 5% bodyweight 32 …”
Section: Metformin Trial Outcomes In Serious Mental Illnessmentioning
confidence: 99%
“…Trials aimed at reversing weight gain typically recruited patients who experienced weight gain of at least 10% bodyweight, although results from a recent pilot RCT conducted in Singapore that included 17 participants suggest that there may be benefits following first episode psychosis for patients with weight gain as low as 5% bodyweight. 32 A caveat for interpreting meta-analysis results is that many do not provide subgroup analyses for those without (and with) diabetes at baseline. Indeed, ten of 17 meta-analyses did not provide baseline descriptions of diabetes status (Supporting Information, supplementary material 1).…”
Section: Metformin Trial Outcomes In Serious Mental Illnessmentioning
confidence: 99%
See 1 more Smart Citation